Antenatal, Intrapartum, and Postnatal Maternal health Care during COVID-19 Pandemic - Alkhazrajy, Lujain Anwar (AL-Kindy College Medical Journal, 2020)
There is limited data and evidence about the effects of COVID-19 on Maternal health, especially when new information is emerging daily, through pregnancy, child birth and post natal period, women are vulnerable to have the infection, this article, aimed to show the suitable measures that should be applied for women at reproductive age who are suspected /confirmed with COVID -19 infection,During pregnancy it is advisable to continue the antenatal care schedule, although reducing face to face visit is recommended (unless the pregnant condition required that ),and prioritize ANC at health facilities for high-risk pregnancy and during second half of pregnancy with adequate infection prevention control  measures.Regarding child birth, positive COVID-19 result without other indications is not an indication to expedite birth, decision for mode of birth not influenced by positive COVID-19 result, it is recommended to support normal labour and if elective caesarean has been planned, epidural anesthesia is highly recommended than general anesthesia. For women with suspected or confirmed COVID-19, Betamimetics: should be avoided as they may exacerbate maternal hypotension, tachycardia and pulmonary edema.Maternal mental wellbeing should be screened in postnatal period because infected women with COVID -19 are more prone to develop an anxiety than general population because of the demands of the disease like  isolation, bereavement, financial difficulties, insecurity and inability to access support systems which are considered as added risk factors to develop mental illnesses